The Whispering Guardian: Religiosity and Internal Whistleblowing in the Realm of ‘Normalized’ Corruption - Maulidi, Ach; Rizal, Ach. Syaiful; Ali Alnajar, Ali Elazumi; Hastuti, Maria Eugenia; Ben Galboun, Abdalmenam Ramadan (Jurnal Aplikasi Manajemen, 2025)
This study aims to fill the theoretical and empirical gaps by investigating whether religiosity can serve as a moral counterforce to perceived risks, or whether corruption weakens its impact, leading to moral disengagement or rationalized silence. This study is unique in its use of Person-Organization fit theory as a conceptual framework. Data for this study were obtained through a structured questionnaire administered to Indonesian public servants. A purposive sampling strategy was employed to select specific local government institutions aligned with the study's objectives. A total of 157 valid responses were analyzed. For the empirical examination, Partial Least Squares Structural Equation Modeling (PLS-SEM) was utilized as the primary analytical technique. These study findings indicate that religiosity has a positive influence on the internal whistleblowing system, suggesting that individuals with strong religious values are more likely to report misconduct. Conversely, corruption negatively affects internal whistleblowing, reinforcing the idea that corrupt environments discourage employees from speaking up. Interestingly, however, corruption does not moderate the relationship between religiosity and whistleblowing. These insights are particularly critical in the present times, as they demonstrate that while corruption weakens whistleblowing overall, it does not diminish the ethical influence of religiosity. This has important implications for policymakers and public institutions in Indonesia and beyond, as it highlights the need to strengthen whistleblowing mechanisms while recognizing the role of personal moral values in fostering ethical behavior.